Analysis and Minimization of the Oscillatory Currents in Multibranch Thyristor-Switched Capacitors. (17th December 2012) - Saied, Mohamed M.
Abstract : This paper addresses the switching transients in multibranch thyristor-switched capacitors (TSCs). The current transients following the addition of a branch to a group of already connected ones are analyzed. Expressions for both its fundamental and its oscillatory components are given in terms of the power network voltage, frequency, short-circuit level, and the switching angle. The relations include also the compensator parameters such as its total reactive power rating, total number of branches, the number of already connected branches, and the initial voltage on the capacitor involved in the switching transient. An expression for the distortion of the supply current is also given. A minimization procedure is presented for identifying the optimal switching angle leading to the least magnitude of the oscillatory current. Switching when the instantaneous supply voltage is equal to the initial voltage will result in the least oscillatory current only in the two special cases of a single-branch compensator, or in the switching of the first branch of a multi-branch TSC. The effect of both the total number of branches and the branch switching steps on the oscillatory current and on the optimal switching angle is also discussed. The advantage of the suggested procedure is demonstrated by investigating several case studies.